Differentiation of Gastric Helicobacter Species Using MALDI-TOF Mass Spectrometry - Berlamont, Helena; De Witte, Chloe; De Bruyckere, Sofie; Fox, James G.; Backert, Steffen; Smet, Annemieke; Boyen, Filip; Haesebrouck, Freddy (Pathogens, 2021)
Gastric helicobacters (Helicobacter (H.) pylori and non-H. pylori Helicobacter species (NHPHs)) colonize the stomach of humans and/or animals. Helicobacter species identification is essential since many of them are recognized as human and/or animal pathogens. Currently, Helicobacter species can only be differentiated using molecular methods. Differentiation between NHPHs using MALDI-TOF MS has not been described before, probably because these species are poorly represented in current MALDI-TOF MS databases. Therefore, we identified 93 gastric Helicobacter isolates of 10 different Helicobacter species using MALDI-TOF MS in order to establish a more elaborate Helicobacter reference database. While the MALDI Biotyper database was not able to correctly identify any of the isolates, the in-house database correctly identified all individual mass spectra and resulted in 82% correct species identification based on the two highest log score matches (with log scores >= 2). In addition, a dendrogram was constructed using all newly created main spectrum profiles. Nine main clusters were formed, with some phylogenetically closely related Helicobacter species clustering closely together and well-defined subclusters being observed in specific species. Current results suggest that MALDI-TOF MS allows rapid differentiation between gastric Helicobacter species, provided that an extensive database is at hand and variation due to growth conditions and agar-medium-related peaks are taken into account.
CRIS-Team WoS Importer:2021-04-09